Equivalent Standard Axle (ESA) pada Jalan Raya Turi, Lamongan, Jawa Timur Menggunakan Metode MDPJ 2017 - Ade Titto Maldini; Ahmad Ridwan; Bobby Damara (Jurnal Talenta Sipil, 2026)
Turi Highway is a vital infrastructure in Lamongan Regency that supports the distribution of agricultural and trade commodities. High traffic intensity, particularly from heavy vehicles, leads to significant pavement damage. This study aims to calculate the Equivalent Standard Axle (ESA) based on actual traffic data and determine the appropriate pavement type using the 2017 Road Pavement Design Manual (MDPJ). A seven-day traffic survey during peak hours was conducted, and the data were converted into Average Daily Traffic (LHR), Passenger Car Unit (SMP), Vehicle Damage Factor (VDF), daily ESA, annual ESA, and Cumulative ESA (CESA) for a 15-year design life. The results showed that the total 6-hour LHR was 15,982 vehicles/day, while the 24-hour LHR was 24,613 vehicles/day. The average daily ESA was 2,070.6, with an annual ESA of 755,769 ESA/year, and a 15-year CESA of 11,336,535. The subgrade CBR value was 6.8%, rounded to 7%, classified as weak soil. Based on these findings, the recommended pavement type is rigid pavement with a 27 cm concrete slab, 10 cm lean concrete, and 15 cm aggregate base layer.